PENGARUH KUALITAS PELAYANAN DAN KEUNGGULAN PRODUK TERHADAP LOYALITAS NASABAH PADA PT. BRI (PERSERO) TBK - Wicaksana, Gilang Adi; Idris, Ahmad; Afrianto, Dadang; Firdaus, Ahmad (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
The purpose of this study was to determine the significant effect of service quality and product excellence on customer loyalty at PT. Bank Rakyat Indonesia (Persero) Tbk Gurah Kediri Work Unit partially and simultaneously in January-May 2020. The type of research used is quantitative research with a causal approach with the research population, namely all customers with a total of approximately 200 customers each month who make loans at PT. Bank Rakyat Indonesia (Persero) Tbk Gurah Work Unit. Data obtained from the results of questionnaires and surveys of research objects. Based on the research, it shows that there is a significant effect partially and simultaneously between service quality and product excellence on customer loyalty at PT. Bank Rakyat Indonesia Tbk, Gurah Kediri Work Unit. This is indicated by the service quality variable with the test results obtained t count 3,871, and product superiority 4,490 <t table 1,662, the F value count 20,138, the value> F table 3,098 and the significance value <significant level that is 0,000 <0.05, then the hypothesis H0 is rejected and Ha is accepted.